Sistema domótico para controlar el acceso de áreas vulnerables de una casa mediante sensores, a través de una aplicación móvil - Rodríguez Caruajulca, José Luis (2018)
A Domotic System is a set of interconnected technologies applied to the control and automation of a house, which allows communication between the user and the system._x000D_ The main objective of the research was to develop a Domotic System that allows_x000D_ controlling access to vulnerable areas of a house. To carry this out, a model of a house in which the system was implemented was made._x000D_ The Domotic System is developed in Arduino and can be accessed through a mobile application, the system provides control making a call to the Smartphone of the owner of the house when an alarm has been activated